Studi Kepustakaan: Pengenalan 4 Algoritma Pada Pembelajaran Deep Learning Beserta Implikasinya - Jamiah Nurhakiki; Yahfizham Yahfizham (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
In the past few years, deep learning has been very popular among IT users. Deep learning is one of the machine learning parts of artificial intelligence (AI). Deep learning has several algorithms in it. So in this paper, we will explain basically about four algorithms owned by deep learning, namely: CNN, RNN, LSTM and SOM along with an explanation of the application of the algorithm. With the explanation, it is hoped that some IT users can understand deep learning algorithms and their implications for work or applications.